Utilization of Palm Oil Mill Effluent for Bio-Extract Production: Physical, Chemical and Microbial Properties, and Application to Growth of Chinese Kale - Saenge Chooklin, Chanika; Khatfan, Akom; Sagulsawasdipan, Kattinat (Science & Technology Asia, 2021)
Palm oil mill effluent is composed of several organic compounds such as nitrogen compounds, oligosaccharides, organic acids, and lipids, which may be beneficial when applied to bio- extracts. The aim of this study was to determine the miscibility of palm waste as an ingredient for bio-extract production; the waste liquid was mixed with two other agricultural wastes: fish waste and pineapple peel. Physical, chemical, and biological changes such as phytotoxicity of the product were observed. Bio-extract fermentation was complete around the end of the first month. The completion of fermentation was determined by the physical, chemical and microbiological features of the mixture. The physical changes of the bio- extract were not significantly different after 35 days of fermentation. Reducing sugar content declined from 66.3 to 2.3 g L-1 over the 150 days of fermentation. COD decreased as well, from 5300 (after secondary treatment) to 200 mg L-1. This could be due to the effect of fermentation on hydrocarbon- based compounds, which are broken down into substances that the microbes are able to digest more efficiently. This bio- extract was subsequently applied to Chinese kale at various dilutions; a dilution ratio of 1: 100 was the most effective for growing Chinese kale. These results indicate that the addition of waste liquids from palm oil factories into bio-extract fermentations could be practical, especially when applied together with fish waste and pineapple peel. The reuse of waste water in bio-extracts could reduce negative impacts on the environment. Moreover, using bio- extracts has the advantage of being lower cost and more environmentally friendly than chemical fertilizers.